خريطة البحوث العلمية في الألعاب اللغوية لتدريس اللغة العربية - Adrizal, Salmi (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This research aims to identify bibliometric data and conduct a critical reflection on studies related to the use of language games as a medium for Arabic language learning. It also aims to determine which titles have high novelty value to serve as a reference for researchers in publishing future scientific works. The researcher employs a library research approach using the Systematic Literature Review method. Data collection was conducted using the Publish or Perish (POP) software, Crossref, and analysis was carried out using the VOSviewer application. The data search was based on the keyword